Synthesis and fabrication of titanium dioxide nanoparticles based biosensor by sol-gel method for E.coli 0157 - Sharipah Nadzirah Syed Ahmad Ayob (Institute of Nano Electronic Engineering, 2016)
This research aims to develop ultrahigh sensitivity and selectivity electrical biosensor as medical diagnostic transducer through integrated IDEs with TiO2 nanoparticles for ultralow concentration and single-mismatch label-free Escherichia coli O157:H7 DNA detection using clinical samples. This objective is accomplished through the following specific objectives to understand the effect of stabilizer during TiO2 solution preparation on the compositions, morphological and electrical properties of the deposited TiO2 nanoparticles synthesized via sol-gel method.